Melatonin loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles reduce inflammation, inhibit apoptosis and protect rat’s liver from the hazardous effects of CCL4 - Alyaa Farid; Valina Michael; Gehan Safwat (Scientific Reports, 2023)
Abstract Liver is an important organ that carries out major important functions including the detoxification of harmful chemicals. Numerous studies have lately focused on the impact of various substances, such as chemical pollutants and pharmaceutical drugs, on the liver. Melatonin (Mel) has been reported for the protection against liver injury. In order to enhance Mel therapeutic benefits and prevent any potential negative effects, Mel has to be delivered to the injured liver. Therefore, the goal of the current investigation was to create Mel-loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles (Mel-PLGA NPs) to alleviate carbon tetrachloride (CCL4)-induced liver damage in male Sprague Dawley rats. The prepared Mel-PLGA NPs were physically characterized to determine its size and charge. Moreover, Mel-PLGA NPs were examined, in vitro, to determine its antioxidant, anticoagulant, anti-inflammatory and cytotoxicity effects before being used in vivo. The effect of NPs on liver injury was evaluated through biochemical, immunological, histopathological examination and flow cytometry technique. Mel-PLGA NPs were smooth and spherical with no signs of aggregation and have in vitro antioxidant, anti-inflammatory and anticoagulant effects. NPs varied in size from 87 to 96 nm in transmission electron microscope images, while their hydrodynamic diameter was 41 nm and their zeta potential was −6 mV. Mel-PLGA NPs had encapsulation efficiency (EE%) and drug loading (DL%) of 59.9 and 12.5%, respectively. Treatment with Mel-PLGA NPs ameliorated all histopathological changes, in liver sections, that resulted from CCL4 administration; where, liver sections of treated groups were similar to those of healthy control GI. NPs administration were superior to free Mel and reversed the elevated levels of liver function enzymes, inflammatory cytokines and matrix metalloproteinases to their normal levels. Moreover, liver sections of groups treated with NPs showed negative immunostaining for nuclear factor-κB (NF-κB) and C-reactive protein indicating their anti-inflammatory behavior. Mel-PLGA NPs significantly protected liver from the toxicity of CCL4. The effective dose of NPs was 5 mg/kg indicating a reduction in the required Mel dose and its associated adverse effects.